Improving Students’ Vocabulary Through Crossword Puzzles for 11th Grade MIPA 3 Students at SMAN 9 Samarinda - Nur Atika; Widi Syahtia Pane; Godefridus Bali Geroda (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The research was prompted by the researcher's teaching internship experience, where they observed that some students had complications mastering English vocabulary. The researcher decided to use crosswords in English learning to enhance students' vocabulary knowledge, as they have a strategic purpose of improving and developing skills. The study aims to describe how crosswords improve students' vocabulary. This study was located at SMA Negeri 9 Samarinda in Class XI – MIPA 3 with 29 students. This research used a two-cycle classroom action research (CAR) method, and the average vocabulary ability of students before class is 49.38. The criteria for success in this research are 75% of students in the class passing the standard minimum criteria (KKM). Cycle I was carried out in two meetings, including a pre-post-test. Started on Monday, March 27, 2023. From cycle I, the results found by researchers were the number of students who passed The Standard Minimum Criteria (KKM) was 20 or 69% of students with an average score of 84.48. The results of the presentation of an improvement in score from the pre-test to the post-test were 0.61%. The increase still did not meet the success target, so the researcher decided to continue the cycle. Cycle II was carried out in two meetings, including a pre-post-test. The cycle started on Monday, April 3, 2023. From cycle II, the results found by the researcher were 27 students with a percentage of 96.3% passing the KKM, and the average post-test results found by the researcher were 94.64. The improvement from the overall mean score in the pre-test to the post-test in cycle II was 10.88%. The classroom action research (CAR) of cycle II was successful and met the requirements of the predetermined criteria. The average score in this study was 75, and 75% of the students in the class completed the KKM. Due to the adjustable of teachers in adapting to classroom conditions and students, crossword puzzles can be a valuable learning tool that enhances their vocabulary skills. Using crosswords in learning can attract students' attention and help them learn more new vocabulary.